Microencapsulation as a novel delivery method for the potential antidiabetic drug, Probucol - Mooranian A; Negrulj R; Chen-Tan N; Al-Sallami HS; Fang Z; Mukkur TK; Mikov M; Golocorbin-Kon S; Fakhoury M; Watts GF; Matthews V; Arfuso F; et al. (Dove Medical Press, 2014)
Armin Mooranian,1 Rebecca Negrulj,1 Nigel Chen-Tan,2 Hesham S Al-Sallami,3 Zhongxiang Fang,4 TK Mukkur,5 Momir Mikov,6,7 Svetlana Golocorbin-Kon,6,7 Marc Fakhoury,8 Gerald F Watts,9 Vance Matthews,10 Frank Arfuso,5 Hani Al-Salami1 1Biotechnology and Drug Development Research Laboratory School of Pharmacy, Curtin Health Innovation Research Institute, Biosciences Research Precinct, Curtin University, Perth, Western Australia, Australia; 2Faculty of Science and Engineering, Curtin University, Perth, Western Australia, Australia; 3School of Pharmacy, University of Otago, Dunedin, New Zealand; 4School of Public Health, Curtin University, Perth, Western Australia, Australia; 5Curtin Health Innovation Research Institute, Biosciences Research Precinct, School of Biomedical Science, Curtin University, Perth, Western Australia, Australia; 6Department of Pharmacology, Toxicology and Clinical Pharmacology, Faculty of Medicine, University of Novi Sad, Serbia; 7Department of Pharmacy, Faculty of Medicine, University of Novi Sad, Serbia; 8Faculty of Medicine, University of Montreal, Montreal, Quebec, Canada; 9School of Medicine and Pharmacology, Royal Perth Hospital, University of Western Australia; 10Laboratory for Metabolic Dysfunction, UWA Centre for Medical Research, Harry Perkins Institute of Medical Research, Perth, Western Australia, Australia Introduction: In previous studies, we successfully designed complex multicompartmental microcapsules as a platform for the oral targeted delivery of lipophilic drugs in type 2 diabetes (T2D). Probucol (PB) is an antihyperlipidemic and antioxidant drug with the potential to show benefits in T2D. We aimed to create a novel microencapsulated formulation of PB and to examine the shape, size, and chemical, thermal, and rheological properties of these microcapsules in vitro. Method: Microencapsulation was carried out using the Büchi-based microencapsulating system developed in our laboratory. Using the polymer, sodium alginate (SA), empty (control, SA) and loaded (test, PB-SA) microcapsules were prepared at a constant ratio (1:30). Complete characterizations of microcapsules, in terms of morphology, thermal profiles, dispersity, and spectral studies, were carried out in triplicate. Results: PB-SA microcapsules displayed uniform and homogeneous characteristics with an average diameter of 1 mm. The microcapsules exhibited pseudoplastic-thixotropic characteristics and showed no chemical interactions between the ingredients. These data were further supported by differential scanning calorimetric analysis and Fourier transform infrared spectral studies, suggesting microcapsule stability. Conclusion: The new PB-SA microcapsules have good structural properties and may be suitable for the oral delivery of PB in T2D. Further studies are required to examine the clinical efficacy and safety of PB in T2D. Keywords: artificial cell microencapsulation, diabetes, antioxidant, anti-inflammatory, Probucol